2017
DOI: 10.3390/s17091938
|View full text |Cite
|
Sign up to set email alerts
|

Basic Simulation Environment for Highly Customized Connected and Autonomous Vehicle Kinematic Scenarios

Abstract: To enhance the reality of Connected and Autonomous Vehicles (CAVs) kinematic simulation scenarios and to guarantee the accuracy and reliability of the verification, a four-layer CAVs kinematic simulation framework, which is composed with road network layer, vehicle operating layer, uncertainties modelling layer and demonstrating layer, is proposed in this paper. Properties of the intersections are defined to describe the road network. A target position based vehicle position updating method is designed to simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…[11], still from a Chinese University, presents a four-layer Connected and Autonomous Vehicles (CAVs) kinematic simulation framework, which is composed with a road network layer, a vehicle operating layer, an uncertainties modelling layer and a demonstrating layer. The properties of the intersections are defined to describe the road network.…”
Section: Review Of the Contributions In The Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…[11], still from a Chinese University, presents a four-layer Connected and Autonomous Vehicles (CAVs) kinematic simulation framework, which is composed with a road network layer, a vehicle operating layer, an uncertainties modelling layer and a demonstrating layer. The properties of the intersections are defined to describe the road network.…”
Section: Review Of the Contributions In The Special Issuementioning
confidence: 99%
“…The proposed special issue has invited submissions related to sensing and connectivity systems for assisted and autonomous driving and for unmanned aerial, underwater and ground vehicles (namely UAV, UUV and UGV) [1,2,3,4,5,6,7,8,9,10,11,12]. Recent studies on the future of the automotive and robotic industry predict that the borders between the ICT (Information and Communication Technology) industry and the consumer industry will blur, and that vehicles will become consumer-centric [13].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al firstly studied driver behavior differences and empirical judgment ratio distributions in an abnormal traffic scenario and then proposed a car-following model for estimating the minimum safety distance for the emergency evacuation vehicle [9]. Similar research studies can be found in [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, subjectively decomposing the road in the vicinity of intersection, into finite segments, within each segment, vehicles operate under different control methods [13]. Researchers segment the intersection connected road into three parts (approach area, adjust area and maintain area), and then guide the vehicles by using the double-loop Spatial Position Associating Time Series (SPATS) method and the Acceleration Dynamically Adjusting based on Predicted Trajectory (ADAPT) method [14]. Slot-based intersections, which could replace traditional traffic lights, have also been implemented to reduce queues and delays.…”
Section: Introductionmentioning
confidence: 99%